The role and elements of social capital of potato farmers in Pattapang Village, Tinggimoncong District, Gowa Regency - Nurbaya Busthanul; Nurdin Lanuhu; Heliawaty Heliawaty; Masyhur Syafiuddin; Andi Kumala Sari (Fakultas Pertanian Universitas Ichsan Gorontalo, 2022)
Social capital is something that is real in everyday life, especially the presence of sympathy, community social relations, and community life that form a social unit. Social capital is meaningful by contributing to the farming community based on the principles of trust, mutual support, and realizing mutual benefits. The purpose of this study was to describe the role and elements of social capital in potato farming in Pattapang Village, Tinggimoncong District, Gowa Regency. The research method uses descriptive qualitative analysis to describe the investment system and the role of social capital. The results of this study show that social capital is beneficial for Potato Farmers in running their farms, then the coordination activities of farmers are able to work together in choosing quality seeds, and farmers are able to make joint decisions so that the choices made are not misguided. With the establishment of good interactions based on the social capital of the Pattapang farming community, it is easier to carry out farming activities and daily life in the community.